LEVERAGING ARTIFICIAL INTELEGENCE TECHNOLOGY: INTRODUCING SPEAK.GOOGLE AS A DIGITAL SPEAKING ASISSTANT FOR EFL STUDENTS - NURMAYASARI, DEWI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2024)
Major contributions have been made by Artificial intelligence (AI) technologies in the development of society. AI-powered assistants become popular among English as a Foreign Language (EFL) students in recent years. AI provides EFL students with more alternatives for customizing their learning experiences. Speak.google is a new tool of Google Search that helps students in learning English by enabling them to practice speaking interactively. The purpose of this study of is to provide an overview of how Speak.google may be used to help EFL students learn English speaking. This study performs descriptive qualitative research. The study shows that Speak.Google is able to help ESL students in learning language by helping them learn and practice English speaking. This AI is providing students with instant feedback and a range of alternate answers. Students can learn to pronounce a sentence and the meaning of each word in sentences. For EFL students who want to improve their English language skills, especially speaking skill, Speak.google is a promising artificial intelligence for them. ABSTRAKKontribusi besar telah diberikan oleh teknologi kecerdasan buatan (AI) dalam perkembangan masyarakat. Asisten yang didukung AI menjadi populer di kalangan siswa pembelajar Bahasa Inggris sebagai Bahasa Asing (EFL) di beberepa tahun terakhir . AI memberi lebih banyak alternatif kepada siswa EFL untuk menyesuaikan pengalaman belajar mereka. Speak.google adalah fitur baru di penulusuran Google yang membantu siswa belajar bahasa Inggris dengan memungkinkan mereka berlatih berbicara secara interaktif. Tujuan dari penelitian ini adalah untuk memberikan gambaran tentang bagaimana Speak.google dapat digunakan untuk membantu siswa EFL belajar berbicara bahasa Inggris. Penelitian ini menggunakan penelitian deskriptif kualitatif. Penelitian ini menunjukkan bahwa Speak.Google dapat membantu siswa ESL mempelajari bahasa dengan membantu mereka belajar dan berlatih berbicara bahasa Inggris. AI ini memberikan siswa umpan balik instan dan berbagai jawaban alternatif. Siswa dapat belajar mengucapkan kalimat dan arti setiap kata dalam kalimat. Bagi pelajar EFL yang ingin meningkatkan kemampuan berbahasa Inggris khususnya kemampuan berbicara, Speak.google merupakan kecerdasan buatan yang menjanjikan bagi mereka.